Relationship between attitudes towards critical thinking and thinking styles on college students in metropolitan Lima - Escurra-Mayaute, Luis Miguel (2008)
To study the relationships between attitude toward critical thinking and the thinking styles on college students of cities of Lima and Callao. It was used Stenberg’s Thinking Style Scale and it was made a Scale about to be Disposed toward Critical Thinking using Samejima’s model. The findings show validity and reliability related to Attitude Toward Critical Thinking Scale and the Thinking Styles Scale respectively. The students score presents a normal distribution shape. There are significative correlations concerning areas of the critical thinking and the thinking styles. There are statistical differences among kind of college, sex, and professional where each scale scores are analyzed.